Mini Review on Emerging Shrimp Diseases in South East Asia - Rocelene Veraann Rukimin; Tamrin Mohammad Lal (2018)
Emerging shrimp disease threats are caused by various etiological agents and are responsible for devastating losses in farmed shrimp around the South Asia and South East Asia. In addition to directly imposing negative economic and ecological effects, these emerging disease outbreaks are also notoriously difficult to prevent and control due to lack of information on the disease itself. The emergence of recent reports in various shrimp diseases are also major concern in shrimp industries and has highlighted some of the difficulties surrounding the diagnosis and control of the diseases. Hence, this paper is intended to provide a review of the literature that focuses on emerging shrimp diseases around South East Asian countries.